Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1896)
Demorest's Family Magazine January, 1896 -- Woman's Industries at the Atlanta Exposition -- Some Recent International Marriages -- When Greek Meets Greek: A Tale of Love and War -- Gathering the Christmas-Trees -- Betty's Papa -- Scarf Pins for Three -- New Thoughts for the New Year -- Society Fads -- Home Art and Home Comfort: Flowers for Wedding and Dinners; Plants for Shady Places Indoors; -- Our Girls: A Case of Conscience -- Earth-Making -- Household: Milady's Tea-Table; Suggestions for Children's Parties; -- Puzzles -- Sanitarian: The Care of the Skin -- What Women are Doing -- The World's Progress: A Successful Philanthropic Plan; A Messiah of the West; The Kaffir Boom; Electricity in Mines; The Mysterious Keely Motor; Suffrage and Divorce in South Carolina; Eugene Field; -- Common Errors In Speech -- Mirror of Fashions -- Correspondence Club -- Gleanings.
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print, Valdosta State University Archives and Special Collections, October 21, 2016.
Keywords: Demorest's Family Magazine; Dressmaking; Magazine; Catalogue; Illustrated Periodicals; Periodicals; Children; Women; Needlework; Travel; Women's History; Social History; Homemaking; Fashion; United States; 1800s; 19th Century; Atlanta Exposition